DAMPAK PANDEMI COVID-19 PADA KESEHATAN MENTAL REMAJA DI KABUPATEN BANGLI - BALI - Rahayuni, I Gusti Ayu Rai; Wulandari, Ida Ayu Putri (Jurnal Riset Kesehatan Nasional, 2021)
Background : The Covid-19 Pandemic situation is an extraordinary event in the world community. In addition to physical impacts due to viruses, the psychological, mental and social impacts was  priority issues  that also involve an adolescents as productive, active and dynamic subjects. Very drastic changes in all settings of life during the lockdown period bring adolescents to the transition situation, a difficulty with social distancing around  more than 3 months which can trigger burden, stress, depression and other mental effects. The purpose of this study was to describe the Impact of Covid-19 Pandemic on Adolescent Mental Health in Bangli District – Bali. Methods :  This descriptive research with cross-sectional approach. Data was collected  at SMA 1 Bangli on July 2020 with a total sampling technique of 302 adolescents who met with inclusion criteria. Data were collected using the Indonesian version of the SRQ-29 questionnaire online and were processed in a descriptive univariate. Results : The results of the study illustrate the conditions during the Covid-19 pandemic that 10 respondents (3%) had undergone Rapid tests, 6 people (2%) had undergone swab tests, 1 person (2%) had confirmed positive Covid-19 and 113 people (37) , 4%) stated that their home area  was once a red zone. Results Analysis of mental conditions during the pandemic that 93 people (30.8%) indicated the presence of neurosis symptoms, 21 people (6.9%) indicated the use of psychoactive substances, 128 people (42.4%) indicated the presence of psychotic symptoms and that is 284 people (94%) indicated PTSD symptoms. Conclusion : Support from all parties through policy, attention and intervention is needed to minimize mental disorders, especially PTSD symptoms in adolescents so that adolescents can back be productive .